2009
DOI: 10.5194/acp-9-175-2009
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of Δ<sup>14</sup>CO<sub>2</sub> across Eurasia: measurements from the TROICA-8 expedition

Abstract: Abstract. Because fossil fuel derived CO 2 is the only source of atmospheric CO 2

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…Such the behavior agrees well with other known observations of surface air composition in northern Eurasia, particularly with the data obtained during TROICA (TRanscontinental Observations Into the Chemistry of the Atmosphere) campaigns being conducted regularly since 1996 on the basis of a mobile carriage observatory along the Trans‐Siberian railroad from Moscow–Vladivostok–Moscow [ Elansky , 2009]. According to the TROICA measurements [ Bergamaschi et al , 1998; Belikov et al , 2006; Turnbull et al , 2009], surface CO concentrations over continental northern Eurasia are much higher in winter, which can be explained mainly by the higher static stability of the lower troposphere, lower OH radical concentrations [ Jaffe et al , 1998; Novelli et al , 1998], and higher anthropogenic emissions from heating [ Holloway et al , 2000]. On the basis of the TROICA measurements, the regions of southern Ural and western Siberia (SWS at Figure 1) were earlier identified as the regions with strong biogenic and anthropogenic emissions of many reactive gases, including nitrogen oxides, methane and carbon monoxide [ Bergamaschi et al , 1998; Hurst et al , 2004; Elansky , 2007].…”
Section: Resultsmentioning
confidence: 99%
“…Such the behavior agrees well with other known observations of surface air composition in northern Eurasia, particularly with the data obtained during TROICA (TRanscontinental Observations Into the Chemistry of the Atmosphere) campaigns being conducted regularly since 1996 on the basis of a mobile carriage observatory along the Trans‐Siberian railroad from Moscow–Vladivostok–Moscow [ Elansky , 2009]. According to the TROICA measurements [ Bergamaschi et al , 1998; Belikov et al , 2006; Turnbull et al , 2009], surface CO concentrations over continental northern Eurasia are much higher in winter, which can be explained mainly by the higher static stability of the lower troposphere, lower OH radical concentrations [ Jaffe et al , 1998; Novelli et al , 1998], and higher anthropogenic emissions from heating [ Holloway et al , 2000]. On the basis of the TROICA measurements, the regions of southern Ural and western Siberia (SWS at Figure 1) were earlier identified as the regions with strong biogenic and anthropogenic emissions of many reactive gases, including nitrogen oxides, methane and carbon monoxide [ Bergamaschi et al , 1998; Hurst et al , 2004; Elansky , 2007].…”
Section: Resultsmentioning
confidence: 99%
“…Most studies ignore the effects of anthropogenic nuclear production of 14 CO 2 on the atmospheric 14 CO 2 since on the global scale this production averages to the smallest contribution, compared to the other terms (Turnbull et al, 2009a) and few try to quantify and correct for it in observations taken nearby nuclear power plants (Levin et al, 2003). However, Graven and Gruber (2011) showed that the regional influence of a dense nuclear power plant network cannot be ignored.…”
Section: The Regional Atmospheric Co 2 and 14 Co 2 Budgetmentioning
confidence: 99%
“…It has subsequently been refined (Meijer et al, 1996;Levin et al, 2003) and used to investigate fossil fuel CO 2 additions on various scales (e.g. Turnbull et al, 2009aTurnbull et al, , 2015Djuricin et al, 2010;Miller et al, 2012;Lopez et al, 2013).…”
Section: Introductionmentioning
confidence: 99%